Insights from precision-cut lung slices—investigating mechanisms and therapeutics for pulmonary hypertension - William R. Studley; Emma Lamanna; Claudia A. Nold-Petry; Cheng Xue Qin; Jane E. Bourke (Respiratory Research)
Abstract Precision-cut lung slices (PCLS) are gaining traction as a versatile ex vivo tool to study mechanisms and treatments for lung diseases. This preparation, in which the major structural elements of the native lung are preserved, bridges the gap between cell and in vivo models allowing researchers to assess integrated functional responses including smooth muscle reactivity, inflammation and tissue remodelling. To date, the application of PCLS to study outcomes relevant to diseases affecting the pulmonary vasculature, such as pulmonary hypertension, is relatively limited compared to those focussed on chronic airway or interstitial lung diseases. This review explores the specific technical requirements for the preparation of PCLS with viable, patent pulmonary arteries, and their application for investigation of mechanisms and treatments related to pulmonary hypertension. Studies characterising vascular responses to contractile agonists in PCLS, particularly in the context of disease-relevant stimuli and models are described, as well as the use of PCLS for the identification of novel vasodilators. This article also outlines current research to prolong PCLS viability and provides directions for future PCLS studies to investigate inflammation and vascular remodelling, with a view to identify therapeutics that address the current limitations of dilator-only treatment of pulmonary hypertension. Overall, the review highlights the importance of PCLS for mechanistic studies and drug development. While PCLS are currently underutilised in the context of pulmonary hypertension, the evidence provided here of the multifaceted functional outcomes that can be investigated using PCLS supports their wider application for understanding disease pathophysiology and validating novel therapeutics.